ANALISIS NILAI GOTONG ROYONG SISWA DALAM EKSTRAKURKULER PRAMUKA - Ferdian Juanda, Muhammad Rafly; Rukmini Handayani; Yuyun Elizbeth Patras (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the implementation of gotong royong attitudes (cooperation, mutual help, responsibility, and solidarity) and to identify their supporting and inhibiting factors in the Scout extracurricular for Siaga Garuda members. This research employed a descriptive qualitative approach at SDN Cimandala 3, Bogor Regency, with the subjects being 18 fourth-grade Siaga Garuda students and two Scout leaders. Data were collected through the triangulation of observation, interviews, and documentation, and subsequently analyzed using an interactive model. The results show that the gotong royong attitudes were effectively instilled through participatory methods such as games, the group system (barung), and direct assignments that build responsibility. The main supporting factors for this success were interactive coaching methods, positive internal responses from students in the form of pride, and a consistent activity environment. However, inhibiting factors were also identified, including individual challenges such as forgetfulness and challenges from social dynamics, such as difficulty cooperating due to personal incompatibility. It is concluded that the success of instilling these attitudes is the result of a synergy between the methods, students' internal motivation, and environmental consistency.